Investigating the Role of Rainfall Variability on the Hydrological Response of Small Tropical Upland Watershed - Christanto, Nugroho; Sartohadi, Junun; Setiawan, Anggri; Hadi, M Pramono; Jetten, Victor; Shrestha, Dhruba Phika (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2019)
Excessive soil losses found in many upper basins in Java which causing severe problem in the lowland areas due to extreme hydrological response. The objective of this research is to study the role of rainfall variability (spatial variability, intensity and duration) on the hydrological response of small tropical upland watershed. To run and test this scenario, a watershed with a good weather dataset and experience soil loss problem was selected. Therefore, Bompon Watershed were selected to perform the model. In order to investigate the hydrological response of different rainfall variability, LISEM was sed. Three scenarios of comparison were designed: different rainfall interpolation, different direction of rainfall movement, high intensity-short duration and low intensity-long duration rain. Initial moisture content (thetai) was found as the most sensitive variable for all indicators when all input variables value increased. When the input variables values decreased, thetai was found as the most sensitive variable for changing in total discharge, whereas saturated hydraulic conductivity (Ksat) was the most sensitive variable for changing in peak of discharge.